Round and spindle cells solid tumor, a morphological variants of angiosarcoma: A case report and review of the literature - Peña-Muñoz, Erika Andrea (2021)
Soft tissue sarcomas represent a clinical and histopathological diagnostic challenge given the low incidence and high variability in clinical presentation, which often makes them unsuspected from the first consultation. A subtype that affects the skin is the idiopathic head and neck angiosarcoma, it represents less than 1% of all soft tissue sarcomas and is characterized by its aggressive biological behavior and early metastatic tendency, features that attribute an ominous prognosis to it. We report the case of a 64-year-old patient with a rapidly growing infiltrating tumor on forehead left side that initially exhibited the morphology of cutaneous lymphoma but with immunophenotyping studies, the diagnosis of cutaneous angiosarcoma was reached.